2018
DOI: 10.1108/hff-04-2018-0160
|View full text |Cite
|
Sign up to set email alerts
|

MHD natural convection of Cu/H2O nanofluid in a horizontal semi-cylinder with a local triangular heater

Abstract: Purpose The purpose of this study is to investigate free convection of copper-water nanofluid in an upper half of circular horizontal cylinder with a local triangular heater under the effects of uniform magnetic field and cold cylinder shell using control volume finite element method (CVFEM). Design/methodology/approach Governing equations formulated in dimensionless stream function, vorticity and temperature variables using the single-phase nanofluid model with Brinkman correlation for the effective dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 37 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…MHD Cu − H 2 O based natural convection in complex shaped enclosure has been reported by Dogonchi et al [54]. A similar study on copper-water nanofluidic flow through a horizontal semi-cylinder has been reported by Dogonchi et al [55].…”
Section: Introductionsupporting
confidence: 62%
“…MHD Cu − H 2 O based natural convection in complex shaped enclosure has been reported by Dogonchi et al [54]. A similar study on copper-water nanofluidic flow through a horizontal semi-cylinder has been reported by Dogonchi et al [55].…”
Section: Introductionsupporting
confidence: 62%
“…Hamilton and Crosser model 49 is used for the effective thermal conductivity of nanofluid as bellow: knfkf=knormalp+(m1)knormalf(m1)φfalse(knormalfknormalpfalse)knormalp+(m1)knormalf+φfalse(knormalfknormalpfalse).where m is the shape factor of the nanoparticles.…”
Section: Numerical Modelmentioning
confidence: 99%
“…We solved Equations (11)-(13) subject to the conditions in Equation (14) via the control-volume-based finite element method (CVFEM) [33][34][35][36]. To ensure mesh independence, Nu ave was obtained for diverse mesh sizes.…”
Section: Numerical Solution and Validationmentioning
confidence: 99%